2021
DOI: 10.1021/acsomega.1c02133
|View full text |Cite
|
Sign up to set email alerts
|

Industrially Produced Fe- and Mn-Based Perovskites: Effect of Synthesis on Reactivity in Three-Way Catalysis: Part 1

Abstract: La0.6Ca0.2Fe0.8Cu0.2O3, undoped (LF) and Ca, Cu-doped (LCFC), powders, obtained by different industrial procedures, are compared to evaluate reproducibility and scale-up in different industrial synthetic approaches: flame spray pyrolysis (FSP) and coprecipitation (COP). Also the effects of varying composition (doping) and FSP process variability are considered as comparative studies on morphological, crystallographic, redox and compositional properties, and functional activity. A model reaction (CO + NO) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The average perovskite composition until a depth of ~1 µm was explored by energydispersive X-ray analysis (EDX), and the average surface composition (depth of 5-10 nm) was explored by X-ray photoelectron spectroscopy (XPS). Element percentages are reported in Table S1 and Table 3, with and without considering the oxygen content, respectively, which is always excessive at the surface as well as in bulk, as usually occurs for perovskite oxides [28,29]. For all samples, all the expected elements (O, La, Mn, Ni/Cu, if any) were detected by both EDX and XPS, without evidence of a significant amount of impurities.…”
Section: Bulk and Surface Compositionmentioning
confidence: 99%
“…The average perovskite composition until a depth of ~1 µm was explored by energydispersive X-ray analysis (EDX), and the average surface composition (depth of 5-10 nm) was explored by X-ray photoelectron spectroscopy (XPS). Element percentages are reported in Table S1 and Table 3, with and without considering the oxygen content, respectively, which is always excessive at the surface as well as in bulk, as usually occurs for perovskite oxides [28,29]. For all samples, all the expected elements (O, La, Mn, Ni/Cu, if any) were detected by both EDX and XPS, without evidence of a significant amount of impurities.…”
Section: Bulk and Surface Compositionmentioning
confidence: 99%
“…Particularly, Rh is one of the most scarce metals, with TWC accounting for more than 80% of total demand because this metal plays a crucial role in the catalytic NO reduction to N 2 . Several attempts have been made in the past to replace this critical metal with other metals, but none have been successful for widespread practical use. The high activity is closely associated with dissociative chemisorption of NO as N s + O s (subscript s is the adsorbed species) on the Rh metal surface. , Theoretical investigations suggested that 3d transition metals (M) including Fe, Co, and Ni also facilitate the cleavage of the N–O bond and the formation of M–N s and M–O s bonds. , However, the as-formed M–N s and M–O s bonds are strong enough to monopolize the surface and hinder catalytic cycles.…”
Section: Introductionmentioning
confidence: 99%